Comparison of the Sensitivity of Crassostrea gigas and Vibrio fischeri (Microtox) for Toxicity Assessment of Produced Water - Augusta Ajuzieogu, Chinyere; Obukowho Odokuma, Lucky (Journal of Advances in Biology & Biotechnology, 2018)
Aim: The toxicity of produced water (untreated and treated) obtained from exploration and production activities of the coast of Nigeria to the oyster (Crassostrea gigas) and a bacterium Vibrio fischeri was assessed. The sensitivity of the toxicity test procedures for both test organisms was assessed. Study Design: Mortality [Lethal concentration (LC50)] for Crassostrea gigas and Inhibition of bioluminescence (Microtox) by Vibrio fischeri [Effective concentration (EC50)] were the toxicity indices employed for the organisms. Place and Duration of Study: Biological monitoring department of Halden Laboratories, Port Harcourt, Nigeria, January, 2016. Methodology: Lethal concentrations (LC50) of C. gigas in produced water generated after 96 hr exposure time were compared with percent reductions in light output by V. fischeri after 15 min exposure time in the microtox assay. Results: The 15 min EC50 values of the untreated and treated produced water samples for V. fischeri was 1.0% and 23.27% respectively, while 96 hr LC50 values of untreated and treated produced water for C. gigas were greater than 1000 parts per thousand (> 1000 ppt). Microtox test indicated the produced water samples were very toxic after 15 min exposure time, while after 96 hrs exposure time C. gigas was yet to produce a toxic response as > 1000 ppt LC50 indicates no toxicity. The microtox EC50 values were one order of magnitude lower compared to those of C. gigas indicating greater sensitivity of microtox assay. Conclusion: Findings from this study therefore support the incorporation and application of microtox test system as a rapid and sensitive bioassay tool in the biological monitoring protocol and ecotoxicological evaluation tests in Nigeria’s petroleum industry.